ANALYSIS OF FARMERS’ SATISFACTION WITH THE ROLE OF LOCAL GOVERNMENT IN DEVELOPING MARKET ACCESS FOR CAVENDISH BANANAS - Sanggra Lasmana; Ridha Rizki Novanda; Hariz Eko Wibowo; Pandu Laksono (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
This study aims to identify the attributes that influence the satisfaction of Cavendish banana farmers and to analyze the level of farmer satisfaction with the role of local government in facilitating market access. The research was conducted in July 2025 in Bajak 2 Village, Merigi Kelindang District, Central Bengkulu Regency, using a census method with 52 farmers as respondents. Data were collected through interviews using a questionnaire based on SERVQUAL dimensions and analyzed using Importance Performance Analysis (IPA) to determine priority attributes for improvement, as well as the Customer Satisfaction Index (CSI) to measure satisfaction levels. The results of the IPA analysis indicate that most attributes influence farmer satisfaction, with a CSI value of 30.18%, which places the level of farmer satisfaction in the “dissatisfied” category. This condition is caused by the low reliability of the local government, slow responsiveness to marketing needs, and the lack of adequate physical facilities and market networks. This study offers novelty by integrating IPA and CSI approaches simultaneously to evaluate the role of local government in facilitating market access for horticultural commodities at the village level. Overall, the role of the local government is considered not yet optimal, thus continuous improvements are necessary.